Ciprofloxacin-Loaded Mixed Polymeric Micelles as Antibiofilm Agents - Rumena Stancheva; Tsvetelina Paunova-Krasteva; Tanya Topouzova-Hristova; Stoyanka Stoitsova; Petar Petrov; Emi Haladjova (MDPI AG, 2023)
In this work, mixed polymeric micelles (MPMs) based on a cationic poly(2-(dimethylamino)ethyl methacrylate)-b-poly(ε-caprolactone)-b-poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA29-b-PCL70-b-PDMAEMA29) and a non-ionic poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) (PEO99-b-PPO67-b-PEO99) triblock copolymers, blended at different molar ratios, were developed. The key physicochemical parameters of MPMs, including size, size distribution, and critical micellar concentration (CMC), were evaluated. The resulting MPMs are nanoscopic with a hydrodynamic diameter of around 35 nm, and the ζ-potential and CMC values strongly depend on the MPM's composition. Ciprofloxacin (CF) was solubilized by the micelles via hydrophobic interaction with the micellar core and electrostatic interaction between the polycationic blocks, and the drug localized it, to some extent, in the micellar corona. The effect of a polymer-to-drug mass ratio on the drug-loading content (DLC) and encapsulation efficiency (EE) of MPMs was assessed. MPMs prepared at a polymer-to-drug mass ratio of 10:1 exhibited very high EE and a prolonged release profile. All micellar systems demonstrated their capability to detach pre-formed Gram-positive and Gram-negative bacterial biofilms and significantly reduced their biomass. The metabolic activity of the biofilm was strongly suppressed by the CF-loaded MPMs indicating the successful drug delivery and release. The cytotoxicity of empty and CF-loaded MPMs was evaluated. The test reveals composition-dependent cell viability without cell destruction or morphological signs of cell death.